Administrative and economic dimensions of regionalization: case of Leningrad Province and North-Western Federal District of Russia - Felix Fedorovich Rybakov; Sergei Felixovich Sutyrin; Nikita Evgenjevich Lisitsyn (European Regional Science Association (ERSA), 2003)
The North-Western Federal District (NWFD) was created in 2000 within the framework of administrative and territorial division reforming. NWFD appeared together with 6 other districts: Central, Privolzhski, Southern, Urals', Siberian and Far Eastern. The District included 2 economic regions: North-Western and Northern and united 11 Federation Units: Kaliningrad, Leningrad, Pskov, Novgorod, Vologda, Murmansk and Arkhangelsk provinces, Karelia and Komi Republics, Nenets Autonomous District and Saint-Petersburg._ According to many indicators North-West Federal District of Russia is a leader of NWFD, leaving behind even Saint-Petersburg (if we compare investment attractiveness, especially for FDI, both domestic and foreign). During 1999 - 2000 several big investment projects started in the Province. The Province's only real competitor among NWFD regions is Novgorod region which also formed an ?oasis' of favorable investment climate within its boundaries._ Economic and geographical significance of Leningrad Province for NWFD and whole Russia is based on transport infrastructure, which develops actively on its territory. The infrastructure includes seaports and railroads that serve as transit bridges between Russia and European countries. That was the reason for the Province's participation in main investment projects in NWFD implemented during the last years, such as creation of Baltic Pipeline System (BPS). BPS project gained national significance; besides, it gave a prominent impact to NWFD fuel industry development. Due to BPS fuel sector companies that operate in oil and gas provinces of Arkhangelsk Province, Komi Republic and Barents and Kara Sea got direct access to seaports on Russian territory._ Interregional relations are developing in other industries as well. New machine-building companies of Leningrad Province start to co-operate with suppliers from other NWFD regions. For example, ?Ford-Vsevolozhsk? company signed a contract with Bor glass factory on automobile glass supplies._ In NWFD interregional relations are intensified by several automobile transport projects. The southern semi-ring of a road bending round the Onega Lake is under construction; the road will connect parts of Leningrad Province and Republic Karelia. Ferry line ?Ust-Luga - Baltijsk - German seaports' will improve transport connection between Leningrad and Kaliningrad Provinces._ But the present intensity of interregional relations within the NWFD is low; non-NWFD regions of Russia and foreign partners of the Province share the bulk of Leningrad Province's external trade. One reason for such a state of affairs the authors tend to find in the drawbacks of a system of territorial and administrative division, which was formed in Russian Federation in early 90-ies. The authors also suggest one possible solution for the problem: consolidation of existing regions - Federation Units. For example, it seems reasonable to form 5 larger regions from 11 existing: Neva Region (Leningrad Province and Saint-Petersburg); Old-Russia Region (Novgorod and Pskov Provinces); Lake Region (Murmansk Province and Republic Karelia); Dvino-Pechora Region (Arkhangelsk and Vologda Provinces, Komi Republic, Nenets Autonomous District); Kaliningrad Province preserves its administrative status. The authors believe, that this reform could help interregional links to surmount this artificial disintegration of the NWFD regions and it would enhance their economic development.
Keywords: 330